Is There any Greater Possibility in Finding HLA-identical Unrelated Hematopoietic Stem Cell Donors among Thalassemia Families for Transplantation of Thalassemia Patients? - Mohyeddin M; Alijanipour P; Alimoghaddam K; Ghavamzadeh A; Khosravi F; Nikbin B. (International Journal of Hematology-Oncology and Stem Cell Research, 2004)
Thalassemia is probably the most common single gene disorder causing a major public health problem in the world. Currently, allogenic hematopoietic stem cell transplantation (HSCT) is the only curative therapy for thalassemia. One major limitation of HSCT is the lack of HLA-identical sibling donors, so attention has turned to finding phenotypically matched unrelated donors."nPatients and methods: From 1991 to 2002, 182 thalassemia patients referred to our center for HSCT. Donor selection was based on HLA class I and class II histocompatibility matching. The results of the serologically HLA class I typing of 549 subjects (patients and their families) and HLA class II typing of 182 patients were compared with HLA class I and II antigens of 100 healthy Iranians normal people. The comparisons between these two groups were tested in univariate analysis, using the Pearson chi-squared statistics."nResults: In comparing, thalassemic families (549 subjects) and healthy Iranians (100 subjects) for HLA class I antigens, significant differences for 11 antigens, including A9 (p= 0.029), A11 (p= 0.01), A19 (p= 0.000), B16 (p= 0.000), B17 (p= 0.029), B27 (p= 0.003), B41(p= 0.000), C2 (p= 0.015), C3(p= 0.012), C4 (p= 0.004), C7 (p= 0.000) were found. For HLA class II antigens, we found that only HLA-DR7 was significantly different (p= 0.002) between 182 thalas-semia patients and the healthy Iranian normal group."nConclusion: In this study, we found that thalassemia families showed significant differences, compared to the healthy Iranian group in several HLA antigens. Comparing HLA polymorphism and finding enough similarity in thalassemia families in the countries, located in the thalassemia belt, may provide benefits for establishing a common HLA bank of thalassemia families.